Effect of Annealing Temperature on Efficiency of Perovskite Solar Cell - Aziz, Issa; Yousif , Kamil; Abdel, Naseem (Journal of Applied Science and Technology Trends, 2020)
In this work, a simple method for producing Perovskite solar cells [PSCs] by recycling automobile batteries is used. Trying to get rid of some structures or materials which are harm to the environment (i.e. recycled car batteries) by using lead [Pb] sheets from those battery. Also, by reusing car batteries we will avoid the disposal of toxic battery elements and provide an alternative technique, readily-available Pb source for fabricating PSCs. Perovskite solar cells [PSCs] were prepared by two-step spin coating solution method grown on the FTO glass substrate. The organo-halide PSCs consists of four layers over FTO glass substrate. Lead iodide (PbI2) and methyl-ammonium iodide (CH3NH3I) used to form the structure of the precursor (CH3NH3PbI3) by the above-mentioned coating method. The photovoltaic performance of PSCs was investigated, together with the stability of PSCs, and the effect of annealing temperature of PRK layer on performance of PSCs. Characterization of PSCs achieved by using X-ray diffraction, SEM, and Spectrophotometer techniques. The effect of annealing on the optical properties of MAPbI3 films were studied by measuring spectral transmittance. The energy band gap value of the MAPbI3 film was found to be 1.60 eV.